Pengaruh Implementasi Hukum Pidana Tehadap Peningkatan Keamanan dan Ketertiban Masyarakat - Yohan Wibisono; Fadjrin Wira Perdana; Irwan Irwan; Doharmam Lumban Tungkup; Miran Miran (CV. Publikasi Indonesia, 2022)
The state has an obligation to create a safe and orderly environment for every citizen. Order and security can form a society with character, mental health and ready to compete in the international realm. This is because the environment has a strong influence on transferring character to each individual. This situation can be realized if the criminal law in Indonesia is enforced properly. Unfortunately, law enforcement sometimes fluctuates so that people are restless and criminals continue to carry out their actions. For this reason, this research was conducted to determine the effect of the implementation of criminal law on increasing public security and order. The research method used is descriptive qualitative research with observation interviews and questionnaires distributed through gform. The results of this study indicate that the implementation of criminal law has a positive effect on increasing public security and order.